Analisis Kemampuan Penalaran Siswa Dalam Menyelesaikan Soal Serupa Pisa Pada Siswa Kelas VIII - Winarti, Sri (2016)
This research aims to know the level of students ' ability in solving math problems similar PISA. This research is a qualitative descriptive study. Research time in thesecond semester in 2014/2015 academic years. Subject research study is a student of SMP Negeri 2 Banyudono class VIII B totaling 30 students. The data collection method used is a method of testing, interviews, observation, and documentation. The validity of the data using triangulation of sources. Data analysis techniques through three grooves of data reduction, data presentation, and conclusion. The test results with the average value of reasoning ability for reproduction 71,1 competencies included in both categories, with 52,2connections competence included in the category enough and to competence 47.6 reflections included in the category enough. According the average score in each competency can be seen that the matter was appropriate level of competence.from the results of the research can be said that a mathematical reasoning ability of the students in doing a similar problem of PISA included in enough categories.